2014
DOI: 10.1071/py13021
|View full text |Cite
|
Sign up to set email alerts
|

Attendance, weight and waist circumference outcomes of patients with type 2 diabetes receiving Medicare-subsidised dietetic services

Abstract: The aim of the present study was to investigate the participation and weight and waist circumference outcomes of patients with type 2 diabetes (T2D) receiving Medicare-subsidised dietetic services. A prospective observational study was conducted between January and September 2011 involving three private practice dietitians who provided services at 11 medical centres in south-east Queensland. All patients with T2D who were referred by their general practitioner (GP) to one of the dietitians as part of their tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Additionally, weight loss and change in BMI were found to have a significant, positive correlation with the number of classes attended immediately following completion of the ESMMWL program and at 6 months. Several other studies have also shown a dose–response effect where weight loss outcomes were improved with higher participation rates .…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, weight loss and change in BMI were found to have a significant, positive correlation with the number of classes attended immediately following completion of the ESMMWL program and at 6 months. Several other studies have also shown a dose–response effect where weight loss outcomes were improved with higher participation rates .…”
Section: Discussionmentioning
confidence: 85%
“…A 2010 qualitative study suggested the CDM scheme wastes public resources, as patients with private health insurance are referred under the scheme, and some patients may return to public services after their consultation cap is reached, duplicating assessments and treatments . Additionally, only one prospective observational study has investigated patient outcomes of dietetics services under the Medicare CDM program, and showed only modest improvements in weight and waist circumference in patients . The capacity of GPs to provide nutrition care is still much greater than dietitians .…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, only one prospective observational study has investigated patient outcomes of dietetics services under the Medicare CDM program, and showed only modest improvements in weight and waist circumference in patients. 20 The capacity of GPs to provide nutrition care is still much greater than dietitians. 21,22 Therefore, instead of increasing schedule fees for allied health services, it could be argued that it would be more economically efficient to put these funds towards supporting GPs and practice nurses to provide nutrition care.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective observational study conducted over nine months found modest changes in weight and waist circumferences for CDM patients with type 2 diabetes. 24 However, there was a high rate of non-attendance (29%) over time. Another recent qualitative investigation found that some CDM patients were motivated by feeling an obligation to attend consultations with allied health professionals due to the rebates available to them.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a continued increase in the overall utilisation of CDM services, minimal evaluation has occurred regarding patient outcomes. One prospective observational study conducted over nine months found modest changes in weight and waist circumferences for CDM patients with type 2 diabetes . However, there was a high rate of non‐attendance (29%) over time.…”
Section: Discussionmentioning
confidence: 99%